Conductive coating for grounding electrode and preparation method thereof

The conductive coating, which is a composite of silicone resin and conductive carbon black/multi-walled carbon nanotubes, solves the problems of conductivity, corrosion resistance and cost in the coating for grounding electrodes, and achieves stable protection in soil environment. It is suitable for grounding electrodes of power and communication towers.

CN121045948APending Publication Date: 2025-12-02THE FIFTH RES INST OF TELECOMM SCI & TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511158075.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing conductive coatings for grounding electrodes suffer from problems such as unstable conductivity, poor mechanical properties, insufficient corrosion resistance, and high cost during long-term use. They are particularly prone to corrosion in soil environments, leading to a deterioration in the current dissipation capacity of the grounding network and posing safety hazards.

Method used

Using silicone resin as the main film-forming resin, combined with conductive carbon black and multi-walled carbon nanotubes, silane coupling agent and titanate catalyst, a specific preparation method is used to ensure uniform dispersion of filler, forming a coating with high conductivity, flexibility and good adhesion, suitable for grounding electrode protection of power and communication towers.

Benefits of technology

It achieves stable electrical conductivity and corrosion resistance over a wide temperature range, reduces coating brittleness, enhances adhesion to metal substrates, is suitable for acid and alkaline environments, and has a low cost, making it suitable for large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045948A_ABST
    Figure CN121045948A_ABST
Patent Text Reader

Abstract

The invention provides a conductive coating for a grounding electrode and a preparation method thereof, and relates to the technical field of industrial coatings. The prepared conductive coating for the grounding electrode has the characteristics of proper flexibility, waterproofness and conductivity and excellent shielding performance, and the low-cost conductive coating preparation method can be applied to grounding electrode protection of electric power and communication iron towers and power transmission and transformation devices; besides, the conductive coating for the grounding electrode uses organic silicon resin as main film-forming resin, and various conductive, reinforcing and anticorrosive fillers, solvents, defoaming agents and the like are added, so that the conductive coating for the grounding electrode is relatively simple in manufacturing process and easy to produce, and has the characteristics of excellent conductivity, low surface energy, good shielding property, good flexibility and the like; the method is suitable for grounding electrode anticorrosion maintenance in a soil environment; meanwhile, good acid and alkali soaking resistance is achieved, the beneficial effects of electrical conductivity, chemical stability and hydrophobicity are achieved, and the method is suitable for large-area application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of industrial coatings technology, and in particular to a conductive coating for grounding electrodes and its preparation method. Background Technology

[0002] A grounding electrode is a metal conductor or group of conductors buried in the soil. It forms a stable electrical connection with the soil through close contact with the earth. It plays a key role in safely dissipating lightning energy and fault current in power systems and communication equipment. Currently, carbon steel or galvanized steel are commonly used as the main material for grounding electrodes in the industry, with a small number of copper or copper-clad steel structures used.

[0003] During long-term operation, the grounding electrode is constantly subjected to multiple erosions such as chemical corrosion, electrochemical corrosion and stray current corrosion due to its long-term exposure to the soil environment. This results in a reduction of the effective cross-sectional area of ​​the metal conductor and the formation of a high-resistivity corrosion product accumulation layer on the surface. This phenomenon directly causes an increase in grounding resistance and a deterioration in the current dissipation capacity of the grounding network. When encountering lightning strikes or short-circuit faults, deteriorated grounding electrodes cannot meet the instantaneous large current discharge requirements, which can easily lead to damage to electrical equipment or even major safety accidents such as personal injury or death. Therefore, it is essential to pay attention to the corrosion and protection of the grounding grid. Among these measures, coating protection is currently the most commonly used and convenient solution for protecting metals from corrosion.

[0004] Conductive coatings used on the surface of grounding electrodes must meet the following requirements: 1. They must have high conductivity (resistivity usually needs to be less than 1Ω·m) to ensure that lightning current is effectively conducted into the ground; 2. When buried in an environment or in contact with air and soil, they must maintain a stable anti-corrosion barrier function under long-term burial or alternating wet and dry environments; At present, the main conductive fillers in conductive anti-corrosion coatings for grounding electrodes are carbon-based conductive materials such as graphite, carbon black, carbon nanotubes and graphene, as well as conductive materials using metal powders such as copper and silver.

[0005] While traditional carbon materials such as carbon black and graphite are inexpensive, sufficient weight percentages are required to ensure conductivity and reach the conductivity threshold. This leads to difficulties in dispersing fillers within the coating, making it prone to agglomeration defects. Furthermore, excessive filling severely degrades the mechanical properties and corrosion resistance of the coating, specifically resulting in increased coating brittleness, decreased adhesion, and susceptibility to cracking and peeling. More seriously, when the coating cracks and exposes the metal substrate, it creates an accelerated corrosion galvanocoupler of "large cathode (coating coverage area) ~ small anode (metal exposure point)," further accelerating localized corrosion and perforation of the grounding electrode. While novel carbon materials such as graphene and carbon nanotubes possess extremely high conductivity (low permeation threshold), they face industrialization bottlenecks such as difficulty in uniformly dispersing in the resin matrix and excessively high costs for large-scale production (especially for graphene).

[0006] While conductive metal powder systems (such as copper powder and silver powder) can provide excellent initial conductivity, their high cost greatly limits their application in large-area coating scenarios such as grounding electrodes. In addition, metal powders (especially copper powder) are prone to oxidation in soil environments, forming high-resistivity oxide / sulfide coatings, which cause the conductivity of the coating to decay rapidly over time. Under electrochemical corrosion, the metal filler itself will also dissolve and be consumed, significantly shortening the protection life.

[0007] In summary, we need to develop a conductive coating for grounding electrodes that combines high conductivity stability, strong corrosion resistance and durability, good process adaptability, and reasonable cost structure, as well as its preparation method. This would solve the vicious contradictions faced by existing conductive and anti-corrosion coatings in practical applications, namely the "carbon-based filler addition amount, mechanical properties, and corrosion resistance," the irreconcilable dilemma of cost and oxidation instability of metal fillers, and the industrialization challenges of dispersion and cost of high-performance nanomaterials. Summary of the Invention

[0008] The purpose of this invention is to overcome the shortcomings of the prior art and provide a conductive coating for grounding electrodes. This conductive coating has excellent flexibility, water resistance, shielding performance, and suitable conductivity. It is a low-cost conductive coating preparation method that can be applied to the protection of grounding electrodes in power and communication towers and power transmission and transformation equipment. In addition, the conductive coating for grounding electrodes uses organosilicon resin as the main film-forming resin and adds various conductive, reinforcing, and anti-corrosion fillers, solvents, defoamers, etc. The manufacturing process is relatively simple and easy to produce. In addition to its excellent conductivity, the product has low surface energy, good shielding and flexibility, and is suitable for the anti-corrosion maintenance of grounding electrodes in soil environments. It also has good resistance to acid and alkali immersion, thus solving the above-mentioned technical problems.

[0009] To achieve the above objectives, this application proposes a conductive coating for grounding electrodes, comprising the following components by weight: 100 parts silicone resin, 10 parts crosslinking agent, 0.5 parts coupling agent, 0.05 parts catalyst, 20 parts conductive filler, 5 parts filler, 100 parts solvent and 0.3 parts defoamer; The coupling agent is a silane coupling agent; the conductive filler is a composite of conductive carbon black and multi-walled carbon nanotubes; and the catalyst is tetrabutyl titanate or tetraisopropyl titanate.

[0010] As a further solution, the silicone resin is a hydroxyl silicone oil with a viscosity of 1500–5000 mm. 2 / s.

[0011] As a further solution, the crosslinking agent is at least one of methyltrimethoxysilane and tetraethyl orthosilicate.

[0012] As a further solution, the silane coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

[0013] As a further solution, the filler is fumed silica and conductive mica powder.

[0014] As a further solution, the solvent is xylene and cyclohexanone.

[0015] As a further solution, the defoamer is a polysiloxane.

[0016] On the other hand, the present invention provides a method for preparing a conductive coating for a grounding electrode, wherein the preparation steps, calculated by weight, include: Place 20 parts of conductive filler, 0.5 parts of coupling agent, 20 parts of silicone resin and 100 parts of solvent into a covered beaker and stir with a magnetic stirrer for 90 to 120 minutes at 2000 rpm to fully disperse the conductive filler. Add the remaining 80 parts of silicone resin to the beaker and continue stirring for 10-30 minutes; Add 0.05 parts of catalyst to the beaker and continue stirring for 10 to 30 minutes; Add 5 portions of filler to a beaker and stir thoroughly for 30–120 minutes; The resulting mixture was wet ball milled to a particle size of 10–30 μm, filtered, and then placed in a new beaker. Add 0.3 parts of defoamer to a beaker and stir thoroughly for 5-10 minutes; Add 10 parts of crosslinking agent to a beaker and stir thoroughly for 5-10 minutes to obtain a conductive coating for the grounding electrode.

[0017] Compared with related technologies, the conductive coating for grounding electrodes and its preparation method provided by the present invention have the following advantages: 1. This invention utilizes silane coupling agents and phthalate catalysts to enhance the adhesion between the coating and the metal substrate. It employs a blend of carbon black and multi-walled carbon nanotubes to improve conductivity, reduce carbon black usage, and minimize carbon black agglomeration, thus reducing the coating's shielding performance. After curing, the surface forms a unique structure with a certain degree of hydrophobicity, enhancing its hydrophobicity in soil environments. The coating film exhibits good resistance to acid and alkali immersion and is suitable for acidic, alkaline, and neutral soil environments. 2. The tetrabutyl titanate or tetraisopropyl titanate catalyst used in this invention replaces the organotin catalyst, reducing environmental pollution. It can also synergistically enhance the adhesion between the conductive coating and the metal substrate with the silane coupling agent. After curing, the organosilicon resin can operate within a wide temperature range of -20℃ to 200℃ while maintaining good toughness and adhesion. When struck by lightning, the temperature rises, but the impact on the coating's performance is minimal. Furthermore, the presence of carbon-based materials provides excellent heat dissipation. In other words, the coating's conductivity and integrity are not compromised when struck by lightning.

[0018] 3. In this invention, carbon black / multi-walled carbon nanotubes are dispersed using a method that involves dispersing both solvent and a portion of resin. During dispersion, the added silane coupling agent interacts with the carbon black / multi-walled carbon nanotubes to form chemical bonds, transforming the inorganic system into an organic system and improving the dispersion effect. The addition of a small amount of resin enhances the shear force of the system, resulting in better dispersion of the carbon black / multi-walled carbon nanotubes and reducing their agglomeration. Attached Figure Description

[0019] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0020] To more clearly illustrate the technical solutions in the embodiments of this application or related technologies, the accompanying drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without creative effort.

[0021] Figure 1 A schematic diagram of the surface morphology of a conductive coating for a grounding electrode provided by the present invention; Figure 2 A schematic diagram of the water droplet state on the coating surface of a conductive coating for a grounding electrode provided by the present invention; Figure 3 This is a schematic diagram of the cross-sectional morphology of a conductive coating for a grounding electrode provided by the present invention.

[0022] The purpose, features, and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0024] Example 1 Embodiment 1 of this application provides a conductive coating for grounding electrodes that combines room temperature curing silicone primer and topcoat and can be applied even with rust, comprising the following components by weight: 100 parts silicone resin, 10 parts crosslinking agent, 0.5 parts coupling agent, 0.05 parts catalyst, 20 parts conductive filler, 5 parts filler, 100 parts solvent and 0.3 parts defoamer; The coupling agent is a silane coupling agent; the conductive filler is a composite of conductive carbon black and multi-walled carbon nanotubes; and the catalyst is tetrabutyl titanate or tetraisopropyl titanate. The organosilicon resin is a hydroxyl silicone oil with a viscosity of 1500–5000 mm. 2 / s; The crosslinking agent is at least one of methyltrimethoxysilane and tetraethyl orthosilicate; The silane coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570; The filler is fumed silica and conductive mica powder; The solvent is xylene and cyclohexanone; The defoamer is polysiloxane.

[0025] The conductive coating for the grounding electrode provided in this embodiment, calculated by weight, includes the following preparation steps: Place 20 parts of conductive filler, 0.5 parts of coupling agent, 20 parts of silicone resin and 100 parts of solvent into a covered beaker and stir with a magnetic stirrer for 90 to 120 minutes at 2000 rpm to fully disperse the conductive filler. Add the remaining 80 parts of silicone resin to the beaker and continue stirring for 10-30 minutes; Add 0.05 parts of catalyst to the beaker and continue stirring for 10 to 30 minutes; Add 5 portions of filler to a beaker and stir thoroughly for 30–120 minutes; The resulting mixture was wet ball milled to a particle size of 10–30 μm, filtered, and then placed in a new beaker. Add 0.3 parts of defoamer to a beaker and stir thoroughly for 5-10 minutes; Add 10 parts of crosslinking agent to a beaker and stir thoroughly for 5-10 minutes to obtain a conductive coating for the grounding electrode.

[0026] It should be noted that: the low surface energy of this coating gives the cured coating a certain degree of hydrophobicity; because the Si-O-- bond energy of organosilicon is higher than that of C-C bonds, it is more stable in conventional acid and alkali chemical media (except hydrofluoric acid), and can maintain good stability and durability in soil environments; and because the galvanized steel flat iron used for the grounding electrode is the most abundant, the special structure of the galvanized steel surface has a certain degree of roughness and texture, which improves the adhesion of the conductive coating of this invention to the galvanized steel. In addition, the conductivity of conductive coatings needs to exceed the critical conductive filler, but if there is too much filler, the coating becomes brittle, hard, or even cracks. Organosilicon coatings have better flexibility and can add more conductive filler than conventional resins to ensure good conductivity and complete film formation.

[0027] Example 2 Based on Example 1, this example uses hydroxyl silicone oil as the organosilicon resin; cyclohexanone and xylene as the solvent in a 1:1 ratio; tetraethyl orthosilicate as the crosslinking agent; silane coupling agents KH560 and KH570 in a 4:1 ratio; conductive mica powder and silica as the filler in a 1:1 ratio; carbon black as the conductive powder; polysiloxane as the defoamer; and tetrabutyl titanate as the catalyst.

[0028] The preparation method is as follows: Step A1: Place carbon black, solvent, silane coupling agent, and 20 parts of hydroxyl silicone oil and solvent into a beaker and stir for 90-120 minutes at 2000 rpm to fully disperse the carbon black.

[0029] Step A2: Based on step A1, add the remaining resin to the beaker and continue stirring for 10 to 30 minutes.

[0030] Step A3: Based on step A2, add the filler to the beaker and stir thoroughly for 30-120 minutes.

[0031] Step A4: Grind the mixture formed in step A3 until the particle size is 10-30 μm, and then filter it.

[0032] Step A5: Place the mixture filtered in step A4 into a new beaker, and add the defoamer and catalyst to the beaker in sequence and stir thoroughly for 5 to 10 minutes.

[0033] Step A6: Add the crosslinking agent to a beaker and stir for 5-10 minutes to obtain the conductive coating.

[0034] The stirring speed involved in steps A2 to A6 is 300 to 1000 rpm.

[0035] Step A7: The substrate to be coated is Q235 hot-dip galvanized flat steel. Clean and wash the surface to remove debris and dust, and dry it with cold air for later use.

[0036] Step A8: Prepare electrode shape molds made of smooth PE or polytetrafluoroethylene material.

[0037] Step A9: Apply the coating obtained in Step A6 directly to the surface of the flat steel in Step A7, ensuring a dry film thickness greater than 300μm. Place it in a normal indoor atmospheric environment and conduct relevant tests after it has fully dried and 3D modeled.

[0038] Step A10: Place the coating obtained in step A6 into the electrode mold of step A8 to form a disc-shaped conductive electrode. Place it in a normal indoor atmospheric environment and carry out relevant testing after it has dried completely in 3D.

[0039] Example 3 Based on Example 1, this example uses hydroxyl silicone oil as the organosilicon resin; cyclohexanone and xylene as the solvent in a 1:1 ratio; tetraethyl orthosilicate as the crosslinking agent; silane coupling agents KH560 and KH570 in a 4:1 ratio; conductive mica powder and silica as fillers in a 1:1 ratio; carbon black and multi-walled carbon nanotubes as conductive powder in a 3:1 ratio; polysiloxane as the defoamer; and tetrabutyl titanate as the catalyst.

[0040] The preparation method is as follows: Step B1: Place carbon black, multi-walled carbon nanotubes, solvent, silane coupling agent and 20 parts of hydroxyl silicone oil into a beaker and stir for 90-120 minutes at 2000 rpm to fully disperse the carbon black and multi-walled carbon nanotubes.

[0041] Step B2: Based on step B1, add the remaining resin to the beaker and continue stirring for 10-30 minutes.

[0042] Step B3: Based on step B2, add the filler to the beaker and stir thoroughly for 30-120 minutes.

[0043] Step B4: Grind the mixture formed in step B3 until the particle size is 10-30 μm, and then filter it.

[0044] Step B5: Place the mixture filtered in step B4 into a new beaker, and add the defoamer and catalyst to the beaker in sequence, stirring thoroughly for 5 to 10 minutes.

[0045] Step B6: Add the crosslinking agent to a beaker and stir for 5-10 minutes to obtain the conductive coating.

[0046] The stirring speed involved in steps B2 to B6 is 300 to 1000 rpm.

[0047] Step B7: Clean and wash the surface of the hot-dip galvanized flat steel to remove debris and dust, and let it dry for later use.

[0048] Step B8: Prepare electrode shape molds made of smooth PE or polytetrafluoroethylene material.

[0049] Step B9: Apply the coating obtained in Step B6 directly to the surface of the flat steel in Step B7, ensuring a dry film thickness greater than 300μm. Place it in a normal indoor atmospheric environment and conduct relevant tests after it has fully dried for 3D.

[0050] Step B10: Place the coating obtained in step B6 into the electrode mold of step B8 to form a disc-shaped conductive electrode. Place it in a normal indoor atmospheric environment and carry out relevant tests after it has dried completely in 3D.

[0051] Example 4 Based on Example 1, this example uses hydroxyl silicone oil as the organosilicon resin; cyclohexanone and xylene as the solvent in a 1:1 ratio; tetraethyl orthosilicate as the crosslinking agent; silane coupling agents KH560 and KH570 in a 4:1 ratio; conductive mica powder and silica as fillers in a 1:1 ratio; carbon black and multi-walled carbon nanotubes as conductive powder in a 1:1 ratio; polysiloxane as the defoamer; and tetrabutyl titanate as the catalyst.

[0052] The preparation method is as follows: Step C1: Place carbon black, multi-walled carbon nanotubes, solvent, silane coupling agent and 20 parts of hydroxyl silicone oil into a beaker and stir for 90-120 minutes at 2000 rpm to fully disperse the carbon black.

[0053] Step C2: Based on step C1, add the remaining resin to the beaker and continue stirring for 10 to 30 minutes.

[0054] Step C3: Based on step C2, add the filler to the beaker and stir thoroughly for 30 to 120 minutes.

[0055] Step C4: Grind the mixture formed in step C3 until the particle size is 10-30 μm, and then filter it.

[0056] Step C5: Place the mixture filtered in step C4 into a new beaker, add the defoamer and catalyst to the beaker in sequence, and stir thoroughly for 5 to 10 minutes.

[0057] Step C6: Add the crosslinking agent to a beaker and stir for 5-10 minutes to obtain the conductive coating.

[0058] The stirring speed involved in steps C2 to C6 is 300 to 1000 rpm.

[0059] Step C7: Clean and wash the surface of the hot-dip galvanized flat steel to remove debris and dust, and let it dry for later use.

[0060] Step C8: Prepare electrode shape molds made of smooth PE or polytetrafluoroethylene material.

[0061] Step C9: Apply the coating obtained in step C6 directly to the surface of the flat steel in step C7, ensuring that the dry film thickness is greater than 300μm. Place it in a normal indoor atmospheric environment and conduct relevant tests after it has dried completely in 3D.

[0062] Step C10: Place the coating obtained in step C6 into the electrode mold of step C8 to form a disc-shaped conductive electrode. Place it in a normal indoor atmospheric environment and carry out relevant tests after it has dried completely in 3D.

[0063] Comparative Example 1 In this comparative example, the organosilicon resin used was hydroxyl silicone oil; the solvent was cyclohexanone and xylene in a 1:1 ratio; the crosslinking agent was methyltrimethoxysilane; the coupling agent was silane coupling agent KH550; the filler was conductive mica powder and silica in a 1:1 ratio; the conductive powder was graphite; the defoamer was polysiloxane; and the catalyst was tetraisopropyl titanate.

[0064] The proportions of each component and the preparation method of the conductive coating in this example are the same as in Example 1.

[0065] Comparative Example 2 In this comparative example, the silicone resin used was hydroxyl silicone oil; the solvent was cyclohexanone and xylene in a 1:1 ratio; the crosslinking agent was methyltrimethoxysilane; the coupling agent was silane coupling agent KH550; the filler was conductive mica powder and silica in a 1:1 ratio; the conductive powder was graphite and multi-walled carbon nanotubes in a 3:1 ratio; the defoamer was polysiloxane; and the catalyst was tetraisopropyl titanate.

[0066] The proportions of each component and the preparation method of the conductive coating in this example are the same as in Example 1.

[0067] The performance of Examples 2-4 and Comparative Examples 1-2 after thorough drying was characterized by performance tests. The test methods and results are shown in Table 1.

[0068] Table 1. Comparison of Test Methods and Results Based on the above test results, the conductive coating obtained by this invention has low surface energy and forms a special structure on the surface after curing. Figure 1 The coating surface morphology has a certain degree of hydrophobicity. Figure 2 The coating surface exhibits water droplet-like characteristics, enhancing its hydrophobicity in soil environments. After film formation, the coating demonstrates good resistance to acid and alkali immersion, making it suitable for acidic, alkaline, and neutral soil environments. The use of silane coupling agents and phthalate catalysts improves the adhesion between the coating and the metal substrate.

[0069] Furthermore, this invention employs a composite of carbon black and multi-walled carbon nanotubes to improve conductivity, reduce carbon black usage, and minimize carbon black agglomeration, thus reducing the impact on coating shielding performance. Excessive carbon black usage results in poor coating shielding performance, and agglomerated carbon black becomes a direct conductive channel for water, ions, and oxygen, accelerating the corrosion of the grounding electrode metal.

[0070] Furthermore, the tetrabutyl titanate or tetraisopropyl titanate catalyst used in this invention replaces the organotin catalyst, reducing environmental pollution. At the same time, it can also synergize with silane coupling agents to enhance the adhesion between the conductive coating and the metal substrate.

[0071] Crucially, this invention employs a method of dispersing carbon black / multi-walled carbon nanotubes using both solvent and a portion of resin. Dispersing with only solvent results in low system viscosity, insufficient shear force, and poor dispersion. During dispersion, the added silane coupling agent interacts with the carbon black / multi-walled carbon nanotubes to form chemical bonds, transforming the inorganic system into an organic system and improving dispersion. Adding a small amount of resin further enhances the system's shear force, resulting in better dispersion of the carbon black / multi-walled carbon nanotubes and reducing their agglomeration. Figure 3 (Coating cross-sectional morphology).

[0072] Furthermore, the silicone resin of this invention, after curing, can operate within a wide temperature range of -20℃ to 200℃ while maintaining good toughness and adhesion. When struck by lightning, the temperature rises, but the impact on the coating's performance is minimal. Additionally, the presence of carbon-based materials provides excellent heat dissipation. In other words, the coating's conductivity and integrity are not compromised when struck by lightning.

[0073] In summary, the organosilicon resin coating system prepared by this invention has the advantages of conductivity, chemical stability and hydrophobicity. The added curing catalyst simultaneously enhances adhesion and can play a good role in conductivity and corrosion prevention in soil or groundwater environments. At the same time, it also reduces the cost of using high-end conductive fillers, making it suitable for large-scale promotion and application. In practical applications, it is still recommended that the coating thickness be above 300μm.

[0074] The above are only some embodiments of this application and do not limit the patent scope of this application. All equivalent structural transformations made under the technical concept of this application and using the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included in the patent protection scope of this application.

Claims

1. A conductive coating for a grounding electrode, characterized in that, Calculated by weight, it includes the following components: 100 parts silicone resin, 10 parts crosslinking agent, 0.5 parts coupling agent, 0.05 parts catalyst, 20 parts conductive filler, 5 parts filler, 100 parts solvent and 0.3 parts defoamer; The coupling agent is a silane coupling agent; the conductive filler is a composite of conductive carbon black and multi-walled carbon nanotubes; and the catalyst is tetrabutyl titanate or tetraisopropyl titanate.

2. The conductive coating for a grounding electrode according to claim 1, characterized in that, The organosilicon resin is a hydroxyl silicone oil with a viscosity of 1500–5000 mm. 2 / s.

3. The conductive coating for a grounding electrode according to claim 1, characterized in that, The crosslinking agent is at least one of methyltrimethoxysilane and tetraethyl orthosilicate.

4. The conductive coating for a grounding electrode according to claim 1, characterized in that, The silane coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

5. The conductive coating for a grounding electrode according to claim 1, characterized in that, The filler is fumed silica and conductive mica powder.

6. The conductive coating for a grounding electrode according to claim 1, characterized in that, The solvents are xylene and cyclohexanone.

7. The conductive coating for a grounding electrode according to claim 1, characterized in that, The defoamer is polysiloxane.

8. A method for preparing a conductive coating for a grounding electrode, characterized in that, The preparation steps, calculated by weight, include: Place 20 parts of conductive filler, 0.5 parts of coupling agent, 20 parts of silicone resin and 100 parts of solvent into a covered beaker and stir with a magnetic stirrer for 90 to 120 minutes at 2000 rpm to fully disperse the conductive filler. Add the remaining 80 parts of silicone resin to the beaker and continue stirring for 10-30 minutes; Add 0.05 parts of catalyst to the beaker and continue stirring for 10 to 30 minutes; Add 5 portions of filler to a beaker and stir thoroughly for 30–120 minutes; The resulting mixture was wet ball milled to a particle size of 10–30 μm, filtered, and then placed in a new beaker. Add 0.3 parts of defoamer to a beaker and stir thoroughly for 5-10 minutes; Add 10 parts of crosslinking agent to a beaker and stir thoroughly for 5-10 minutes to obtain a conductive coating for the grounding electrode.